Tradisi Mekotek Sebagai Gambaran Nilai Sosial Dan Humaniora Dalam Kehidupan Masyarakat Desa Munggu - Yulia Putri, Ni Made Dwi; Utami, Anak Agung Istri Dewi Adhi (Program Studi PPKn Universitas Pendidikan Ganesha, 2026)
Tradition is part of the cultural heritage that is passed down from generation to generation and becomes a social identity and a form of local wisdom of a community. One tradition that still survives today is the mekotek tradition, which is carried out by the people of Munggu Traditional Village, Badung, Bali. The purpose of this study is to describe the implementation of the mekotek tradition, examine the values contained in it, and describe the form of preservation by the community. The method used in this article is a literature study through literature analysis from relevant journals, books and scientific articles. The results of the study show that the mekotek tradition not only has historical value as a symbol of repelling bad luck, but also contains social values such as mutual cooperation, togetherness, spirituality, and solidarity. These values strengthen the social structure of the community and reflect the harmony of life between citizens, the preservation of this tradition is a collective effort of the community in maintaining cultural heritage so that it remains alive in the midst of dynamic times.